2018
DOI: 10.3390/met8060401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basketweave Microstructure on Very High Cycle Fatigue Behavior of TC21 Titanium Alloy

Abstract: This paper discusses the effect of basketweave microstructure on the very high cycle fatigue behavior of TC21 titanium alloy. Ultrasonic fatigue tests at 20 kHz are done on a very high cycle fatigue (VHCF) property of the alloys with 60 µm and 40 µm basketweave size, respectively. Results show that the alloys illustrate step-wise S-N characteristics over the 10 5 -10 9 cycle regimes and that fatigue fracture in both of the alloys occur beyond the conventional fatigue limit of 10 7 cycles. Subsurface crack init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…However, the completely opposite result, the bimodal microstructure presented a higher VHCF strength than the fully lamellar microstructure, was reached by Zuo et al 12 and Crupi et al 19 Moreover, Liu et al 18 discovered that the VHCF strength of the bimodal microstructure was similar to that of the equiaxed microstructure. The miniaturization of microstructure was beneficial to enhance the VHCF resistance 17,20 . Summarized, the relationship between VHCF strengths and microstructure characteristics is intricate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the completely opposite result, the bimodal microstructure presented a higher VHCF strength than the fully lamellar microstructure, was reached by Zuo et al 12 and Crupi et al 19 Moreover, Liu et al 18 discovered that the VHCF strength of the bimodal microstructure was similar to that of the equiaxed microstructure. The miniaturization of microstructure was beneficial to enhance the VHCF resistance 17,20 . Summarized, the relationship between VHCF strengths and microstructure characteristics is intricate.…”
Section: Introductionmentioning
confidence: 99%
“…Crupi et al [31] obtained similar results through investigating the VHCF behavior of Ti-6Al-4V alloy produced by two forging processes. Recently, Nie et al [32] studied the fatigue performance of TC21 titanium alloy with two sizes of basketweave in the life span of 10 5 -10 9 . They pointed out that the fatigue property of the short size basketweave is higher.…”
Section: Introductionmentioning
confidence: 99%
“…However, Krahmer et al [5] takes the surface integrity and surface state as the consideration point, and abrasive water jet, wire electrodischarge machining, laser to replace the traditional milling processing of tensile samples, shortening the processing time and having great industrial value in industrial applications, In practical application literature [6][7][8][9], ball-burnishing means can be adopted to significantly improve the surface quality of materials, so as to improve the corrosion resistance and wear resistance of materials and reduce the wear ratio of materials. In terms of material fatigue, Nie et al [10] the surface state of titanium alloy after polishing can affect crack initiation in the fatigue process, thus affecting the fatigue performance of the material. Torres et al [11] found that micro-cracks formed on the surface of AISI 4340 steel during shot peening would have an impact on the initiation location of cracks.…”
Section: Introductionmentioning
confidence: 99%